Pengaruh Cita Rasa dan Pelayanan terhadap Kepuasan Pelanggan pada Rumah Makan Lontong Tahu dan Nasi Pecel di Karangjati Kabupaten Semarang - Eva Alya Mujahadah; Riyono Riyono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Located in Karangjati, Semarang Regency. The rapid development of the culinary industry has led to increasingly fierce competition. Customer satisfaction is crucial for business continuity. This study employs a quantitative method with an explanatory design. A total of 96 individuals were surveyed using simple random sampling. The F-test, reliability test, multiple linear regression, coefficient of determination, descriptive statistics, and t-test were used to analyse the data collected via a Likert scale questionnaire. The results show that taste and service quality have a positive and significant effect on customer satisfaction. Consistency in taste provides emotional satisfaction, while good service enhances the customer's dining experience. The coefficient of determination shows that these two factors explain more than 60% of the variation in customer satisfaction. These findings emphasise the importance for traditional restaurants to maintain the uniqueness and consistency of taste while improving service quality in order to build customer loyalty and maintain competitiveness.